Perilaku Berwisata Wisatawan Milenial Di Daya Tarik Wisata Pantai Pandawa, Kabupaten Badung, Bali - Darmiati, Kadek; Oka Mahagangga, I Gusti Agung (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2023)
The COVID-19 pandemi situation has made Indonesia's tourism trend move massively towards new tourism, namely trends that prioritize personalized, customized, localized, and smaller sizes. After the COVID-19 pandemi, the tourism industry experienced a change in trend that was inseparable from the emergence of new patterns of behavior in society that pay more attention to health and safety in carrying out tourism activities and changing people's needs in planning their holidays. Especially for the millennial generation who have a great curiosity, so that they sometimes go beyond the boundaries of the habits of previous generations. Especially when it comes to traveling or taking advantage of free time. This study aims to identify the behavior of millennial tourists at the Pandawa Beach Tourist Attraction after the COVID-19 pandemi. This study uses mixed research methods (qualitative and quantitative) with data collection techniques namely, observation, interviews, questionnaires and literature study. The results of the analysis obtained show that the behavior of millennial generation tourists in traveling tends to be very "dependent" on information and technology. The millennial generation's dependence on technology influences the way they travel, starting from the dreaming, planning, booking, experience, and sharing phases. The convenience offered by technology makes consumption patterns of millennial tourists shift to OTA and also tend to choose natural tourism destinations. Keyword: tourist behavior, millennial tourists, tourist attraction.